2023
DOI: 10.1186/s12969-023-00820-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of coronary artery lesions in chinese pediatric Takayasu arteritis patients: a retrospective study

Abstract: Backgroud To summarize the clinical characteristics and identify the risk factors for pediatric Takayasu arteritis (TAK) with coronary artery lesions (CALs). Methods Clinical data of pediatric TAK patients in our center were retrospectively assessed. Independent risk factors for CALs were identified using multivariate logistic regression analysis. Survival analysis was used to compare differences in survival rates between the groups. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hence, imaging studies play a crucial role in diagnosing and monitoring the disease [ 56 ]. Studies have shown that children with TAK with CAL have higher levels of leukocytes, platelets, C-reactive protein, tumor necrosis factor-α (TNF-α), and interleukin-2 receptor (IL-2R) compared to those without lesions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, imaging studies play a crucial role in diagnosing and monitoring the disease [ 56 ]. Studies have shown that children with TAK with CAL have higher levels of leukocytes, platelets, C-reactive protein, tumor necrosis factor-α (TNF-α), and interleukin-2 receptor (IL-2R) compared to those without lesions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Xu et al [ 31 ], all 26 pediatric TAK patients were treated with GCs precombined with infliximab and MTX, TCZ and MTX, and cyclophosphamide (CP) in 17 (65.4%), 2 (7.7%), and 5 (19.2%) cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations